Integrasi Teknologi Informasi dalam Strategi Manajemen Keberlanjutan - Rosa Christiana Esti Noor Sumaryanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this research is to explore the integration of information technology (IT) into sustainability management strategies across various industrial sectors. With increasing awareness of the importance of sustainability, companies are being urged to adopt more efficient and transparent practices. The research methodology used was a mixed approach, including surveys, in-depth interviews, and document analysis to collect primary and secondary data. The results indicate that companies that adopt IT in their sustainability strategies experience significant increases in operational efficiency and waste reduction. For example, a report from the International Data Corporation (IDC) states that 70% of companies implementing advanced IT solutions report a 30% increase in operational efficiency and a 30% reduction in waste within three years. The implications of this research suggest that despite challenges in IT integration, companies can achieve significant benefits in achieving sustainability goals through the use of appropriate technology and adequate employee training. This research is expected to provide practical recommendations for companies seeking to improve their sustainability performance through information technology integration.